Improving access to health care for people with severe chronic obstructive pulmonary disease (COPD) in Southern New Zealand: qualitative study of the views of health professional stakeholders and patients - Tim Stokes; Fiona Doolan-Noble; Emma Tumilty; Anna Tiatia Fa'atoese Latu; Jo Baxter; Kathryn McAuley; Debbie Hannah; Simon Donlevy; Jack Dummer (BMJ Open)
Objectives Chronic obstructive pulmonary disease (COPD) is a common chronic disease with significant morbidity and mortality, particularly for Māori, which places a large burden on the New Zealand (NZ) health system. We undertook a qualitative study as part of a mixed-methods implementation research project which aimed to determine the barriers and enablers to the provision of accessible high-quality COPD care.Setting Southern Health Region of NZ (Otago and Southland).Participants Thirteen health professional stakeholders and 23 patients with severe COPD (including one Māori and one Pasifika participant).Methods Semistructured interviews were undertaken. A thematic analysis using the Levesque conceptual framework for access to healthcare was conducted.Results Health professional stakeholders identified barriers to providing access to health services, in particular: availability (inadequate staffing and resourcing of specialist services and limited geographical availability of pulmonary rehabilitation), affordability (both of regular medication, medication needed for an exacerbation of COPD and the copayment charge for seeing a general practitioner) and appropriateness (a shared model of care across primary and secondary care was needed to facilitate better delivery of key interventions such as pulmonary rehabilitation and advance care planning (ACP). Māori stakeholders highlighted the importance of communication and relationships and the role of whānau (extended family) for support. Patients’ accounts showed variable ability to access services through having a limited understanding of what COPD is, a limited knowledge of services they could access, being unable to attend pulmonary rehabilitation (due to comorbidities) and direct (medication and copayment charges) and indirect (transport) costs.Conclusions People with severe COPD experience multilevel barriers to accessing healthcare in the NZ health system along the pathway of care from diagnosis to ACP. These need to be addressed by local health services if this group of patients are to receive high-quality care.